'Pragmatic randomized controlled trial of individually prescribed exercise versus usual care in a heterogeneous cancer survivor population': a feasibility study PEACH trial: prescribed exercise after chemotherapy. - Guinan, Emer; Broderick, Julie; Hussey, Juliette (My University, 2010)
BACKGROUND: Many cancer survivors suffer a range of physical and psychological symptoms which may persist for months or years after cessation of treatment. Despite the known benefits of exercise and its potential to address many of the adverse effects of treatment, the role of exercise as well as optimum duration, frequency, and intensity in this population has yet to be fully elucidated. Many cancer rehabilitation programmes presented in the literature are very long and have tight eligibility criteria which make them non-applicable to the majority of cancer survivors. This paper presents the protocol of a novel 8-week intervention which aims to increase fitness, and address other physical symptoms in a heterogeneous cancer survivor population. METHODS/DESIGN: The aim is to recruit 64 cancer survivors 2-6 months after completion of chemotherapy, usually adjuvant, with curative intent. Subjects will be recruited through oncology clinics in a single institution and randomised to usual care or an exercise intervention. The exercise intervention consists of two specifically tailored supervised moderate intensity aerobic exercise sessions weekly over 8-weeks. All participants will be assessed at baseline (0 weeks), at the end of the intervention (8 weeks), and at 3-month follow-up. The primary outcome measure is fitness, and secondary patient-related outcome measures include fatigue, quality of life, and morphological outcomes. A further secondary outcome is process evaluation including adherence to and compliance with the exercise program. DISCUSSION: This study will provide valuable information about the physical outcomes of this 8-week supervised aerobic programme. Additionally, process information and economic evaluation will inform the feasibility of implementing this program in a heterogeneous population post cessation of chemotherapy.
PUBLISHED
Keywords: Physiotherapy; Cancer